Studi Komparatif Perpajakan dalam Sharing Economy : Studi Kasus Jasa Angkutan Berbasis Online - Bellinda Aurellia; Bina Meidiana Sari; Angelin Dena Rony (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
New innovation and technology that was born together with 4th Industrial revolution triggered the disruption in various aspect of human life. In Indonesia, one of the most prominent disruption is within the transportation industry. The assimilation of technology and conventional transportation method gave birth to various financial technology that provides online-based transportation such as Gojek, Grab, and Uber. China is the country with the highest revenue generated from the industry. In Southeast asia, other than in Indonesia, the industry also growing fast in Singapore, Malaysia, and Vietnam. This research intend to find out the taxation regulation applied to ride-hailing services in the four countries mentioned using literature study. From the research, it can be concluded that China, Singapore, Vietnam, and Malaysia has had taxation regulation for ride-hailing services. Tax collection in Singapore has been working finely with the regulation applied, but problems arise in China, Vietnam, and Malaysia in the terms of tax rate for the drivers and tax rate for the firms because of the drivers and firms ambiguous classification as a tax subject.